Peranan Kepala Desa dalam Menyelesaikan Sengketa Warisan di Desa Tonrong Rijang Kecamatan Baranti Kabupaten Sidenreng Rappang - Windy WInata (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research entitled “The Role of Village Chief in Finalizing Inheritance Lawsuit at Tonrong Village in Baranti District” is backed by the assumption of inheritance problems would keep going on ages of time. The Chief of Village is held responsible to maintain his people’s life condusive by judging any lawsuits, particularly for people at Tonrong Rijang village, district of Baranti, region of Sidenreng Rappang. The main problem to keep focused in is as follows: (1) How is Chief of Village role in finalizing inheritance lawsuit at Tonrong Rijang village; (2) What factors are involved in Chief of Village role of finalizing inheritance lawsuit at Tonrong Rijang village. Achieving the answers would need observation, questionnaire, interview, and literature study methods. This research would use analysis method of descriptive-qualitative, which based on field data and literature study. The answers achieved are as follow: (1) The Chief of Village is fully in charge to settle inheritance lawsuit by studying the mentioned family tree; informations on lawsuit origins; facilitating several meetings and conferences; proposing an alternative to solve the problem; and giving needed advices. (2) The resisting factors are as follow: hard to track the situation of the inheritance properties (1,30%); so little witnesses (1,53%); the human factor (1,37%); and uncertified land rights mutation (1,58%). The leading factors are as follow: The Chief of Village has a great power (3,53%); people in the village feels ashame of inheritance lawsuit (1,79%); the conference was held by familiarity in mind (3,65%); and the lawsuit through legal council seems complicated, overpriced, and took a long time to settle (1,95%).